الفهرس العام لمخطوطات المكتبة البارونية - الباروني, سعيد بن يوسف (2019)
Keywords: Bibliothèques – Djerba; Catalogue – Djerba; Manuscrits – Djerba

Le catalogue de la bibliothèque al-Bāsī : circulation et thésaurisation du savoir à Djerba - Madani, Sarra (Ecole Pratique des Hautes Etudes, 2019)
Don de l'auteure
Keywords: Basi; mosquée al- (Oualegh; Djerba); Bibliothèques – Djerba; Manuscrits – Djerba

al-Maktabat al-Bārūniyya bi-Jarba - Assidje (al-Jazira, 2014)
Keywords: Bibliothèques – Djerba

‏التعريف بالمكتبة البارونية بجربة - الباروني, سعيد بن يوسف (Patrimoine et Créativité, 2018)
Keywords: Bibliothèques – Djerba

The (Almost) Lost Siyar of Jabal Nafusa | سير مشائخ جبل نفوسة (التي كادت تُفقد) - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2016)
Keywords: Bibliothèques – Djerba; Manuscrits – Djerba; Prosopographie – Djebel Nefousa

Al-Bārūnī Library in Djerba | فتح المكتبة البارونية في جربة - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2016)
Keywords: Bibliothèques – Djerba

Barouni Manuscript Library, a Livre d'Or | المكتبة البارونية: كتاب التسجيل - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2015)
Keywords: Bibliothèques – Djerba

Cheikh Salim Seminar in Djerba & the Salim b. Yaʿqūb Library | ملتقى الشيخ سالم الثقافي في جربة ومكتبة سالم بن يعقوب - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2015)
Keywords: Bibliothèques – Djerba

Association pour la sauvegarde de l'île de Djerba (Part 1): Manuscripts | جمعية صيانة جزيرة جربة (الجزء الأول): المخطوطات - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2014)
Keywords: Bibliothèques – Djerba; Manuscrits – Djerba

Some Observations on Watermarks from the Barouniyya Library | ملاحظات حول العلامات المائية من المكتبة البارونية - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2014)
Keywords: Bibliothèques – Djerba; Manuscrits – Djerba

Oddments from a “Nukkārī” Ibadi Library: the al-Ṣāṭūrī Library in Jerba, Tunisia | بقايا من مكتبة “نكارية”: مكتبة الصاطوري بجزيرة جربة (تونس) - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
Over the past several years, I have worked with private manuscript collections belonging to families in Jerba, Tunisia. The island is home to several well-known libraries, including those belonging…
Keywords: Bibliothèques – Djerba; Nukkarisme

Intersections between Manuscript and Lithograph Cultures in Private Libraries | التداخلات بين ثقافتَي المخطوطات والطبعات الحجرية في المكتبات الخاصّة - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
Historians interested in Ibadi and other Arabic manuscripts (including me) often treat manuscripts separately from printed materials in private libraries. But in the second half of the 19th century…
Keywords: Bibliothèques – Djerba

Announcing a new manuscript conservation effort in Djerba, Tunisia: the El Bessi Library Project | إعلان بمشروع جديد للحفظ على المخطوطات في جزيرة جربة: مشروع مكتبة جامع الباسي - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2017)
Keywords: Bibliothèques – Djerba; Manuscrits – Conservation; Manuscrits – Djerba

Djerba : Renaissance de la bibliothèque Al Barounia - Kapitalis - Bouabid, Naceur (Kapitalis, 2016)
Al Barounia est une nouvelle bibliothèque, qui a été inaugurée, samedi 5 mars courant, à Houmt-Souk, chef lieu de l’île de Djerba : un patrimoine livresque inédit sort de l’ombre.
Library Catalog: kapitalis.com
Keywords: Bibliothèques – Djerba

مدرسة جامع الباسي العلمية من خلال كتابات الشيخ سالم بن يعقوب.. من النشأة إلى الأفول - البوجديدي, علي (المواقع والمعالم بجزيرة جربة وتخومها‏: ‏دراسات ضمن ملتقى البشير التليلي في التاريخ والحضارة، الدورة الرابعة عشرة, 2019)
Keywords: Bibliothèques – Djerba

‏فهرس مخطوطات المكتبة البارونية لمؤسسها الشيخ سعيد بن عيسى الباروني (1188-1281هـ/1775-1865) ‏القسم الاباضي - سيوسيو, صالح بن بكير; بوسنان, محمد بن عمر (المكتبة البارونية, 2018)
Keywords: Bibliothèques – Djerba; Catalogue – Djerba; Manuscrits – Djerba

المخطوط بجزيرة جربة تراث منسي : مجموعة الباسي للمخطوطات من النسيان إلى الفهرسة - البوجديدي, علي (2018)
Keywords: Bibliothèques – Djerba

مخطوطات عمانية في خزانة سالم بن يعقوب الجربي - العيسري, محمد بن عامر (الذاكرة, 2019)
Keywords: Bibliothèques – Djerba; Manuscrits – Djerba

Preliminary Catalog of Arabic Manuscripts at the Association pour la Sauvegarde de l’Île de Djerba (Houmet Souk, Tunisia) - Love Jr, Paul M. (2018)
This a preliminary catalog of the Arabic manuscripts held at the Association pour la Sauvegarde de l’Île de Djerba (ASIDJ) on the island of Djerba, Tunisia. These manuscripts (bound volumes and assembled collections of fragments, representing many more titles) are all stored in acid-free boxes or folders. All items are housed in the association’s library in a former zawiya in the city of Houmet Souk. The association also has a sizeable collection of family and other documents in manuscript form that are awaiting cataloging—in case you are interested! Many of the manuscripts carry content related to the history of Ibadism (e.g. MS 013) and the history of Djerba (e.g. MS 01). For example, chronicles or legal compendia containing cases of disputes in Djerba, where there has been a sizeable Ibadi population for centuries.
Keywords: Bibliothèques – Djerba; Catalogue – Djerba; Manuscrits – Djerba

What the flames missed: traces of al-Baʿṭūrī Arabic manuscript library in Jerba, Tunisia - Love Jr, Paul M. (Études et Documents Berbères, 2018)
Keywords: Bibliothèques – Djerba

Écouter le conte d’un manuscrit penser avec une copie d’une chronique ibadite de la bibliothèque Barouni à Djerba - Love Jr, Paul M. (Études et Documents Berbères, 2016)
Keywords: Bibliothèques – Djerba

The Sālim Bin Yaʿqūb Ibāḍī Manuscript Library in Jerba, Tunisia: A Preliminary Survey & Inventory - Love Jr, Paul M. (Journal of Islamic Manuscripts, 2017)
Keywords: Bibliothèques – Djerba

Aperçu des stratégies des communautés ibadites du Maghreb dans la conservation et la valorisation du patrimoine manuscrit - Mestaoui, Soufien (Horizons maghrébins, 2017)
Keywords: Bibliothèques – Djerba; Bibliothèques – Mzab; Manuscrits – Djerba; Manuscrits – Mzab